The provision of pharmaceutical advice improves patient vaccination status - Fuchs J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Aim: To increase vaccination rates in the wealthy industrial nation of Germany. For a variety of reasons there is a substantial deficit in the number of individuals who receive vaccinations in comparison with other industrialized countries.Methods: In Autumn 2003, a regional vaccination consultation was initiated over a five-week period. Individuals involved in the study provided general information, including their age, health status, and vaccination records, and received an extensive consultation in a pharmacy in Jena, Germany. Participants were provided with a written overview of their vaccination status. After approximately five weeks, the vaccination status of each individual was recorded.Results: 312 of 2500 patients received intensive vaccination education based on their accompanying vaccination documentation. Older individuals, who are known for having the largest vaccination gap in Germany, represented the highest percentage of people who used this service. The five most commonly required vaccinations had increased significantly, five weeks after the consultation. These vaccination rate increases included diphtheria, which rose from 55.8 to 71.2%, tetanus, which rose from 73.1 to 86.5%, influenza, which rose from 46.5 to 74.7%, pneumococcal, which rose from 32.4 to 62.8%, and tick-borne encephalitis, which rose from 31.9 to 42.4% (all p=0.008).Conclusions: Well structured vaccination consultations help to raise vaccination rates. Thus, pharmacies should consider offering and implementing this preventive measure so as to lower the rates of preventable disease and to save costs.